An evaluation of the question types used by criminal justice professionals with complainants in child sexual assault trials - Powell, Martine B. (Journal of criminology, 2022)
The way that complainants of child sexual assault are questioned about their experiences can profoundly influence the accuracy, credibility, and consistency of their evidence. This is the case for all people, but especially children whose language, social, and cognitive capacity is still developing. In this study, we examined the questions used by a representative sample of Australian prosecutors, defense lawyers, and judges/magistrates to determine if this is an area that warrants improvement. Our focus was the type of questions used by the different professionals and how (if at all) these varied across complainant age groups (children, adolescents, and adults, total N?=?63). Our findings revealed that each complainant group was questioned in a manner known to heighten misunderstanding and error (e.g., complex and leading questions were used frequently by all professional groups). There was also little indication of question adaption according to age (e.g., prosecutors asked children more complex questions than they asked adults). When the results are considered in the context of the broader literature on the impact of different question styles, they suggest that professional development in questioning would improve the quality of trial advocacy and judicial rulings.